2021
DOI: 10.1145/3447790
|View full text |Cite
|
Sign up to set email alerts
|

Distributed interaction design

Abstract: Creating user interfaces that are natural, guessable, learnable, memorable and accessible is a persistent challenge.Involving end users in the design process is a well-established approach to address these challenges, but traditional participatory design has limitations, especially when it comes to scaling beyond the lab and reaching diverse participants. I build on the success of a popular participatory design method called end-user elicitation. Elicitation studies work by presenting the effect of an interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In our study, we found that the participants were proficient in using both systems, successfully discovering the majority of the gestures required to activate the system functions. In summary, whereas the prior work used identification studies to evaluate the results of elicitation studies [4,15], we show that identification studies can be used as an alternative to elicitation studies to craft gesture-based interfaces, enabling the interaction designers to harness the advantages of in situ observations, as well as the cost-effectiveness and speed [16] offered by crowd-sourcing platforms.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In our study, we found that the participants were proficient in using both systems, successfully discovering the majority of the gestures required to activate the system functions. In summary, whereas the prior work used identification studies to evaluate the results of elicitation studies [4,15], we show that identification studies can be used as an alternative to elicitation studies to craft gesture-based interfaces, enabling the interaction designers to harness the advantages of in situ observations, as well as the cost-effectiveness and speed [16] offered by crowd-sourcing platforms.…”
Section: Introductionmentioning
confidence: 90%
“…This allows the researchers to collect the symbols most preferred by their potential user base; the overarching idea is that such symbols are preferable to those created by HCI professionals alone [24]. However, the traditional in-lab elicitation studies face limitations related to their sample populations; these are often composed of potential users available on university campuses, which may not be representative of a wide range of users [4,15]. To overcome these limitations, Ali et al [4] proposed conducting elicitation studies using a custom-made crowd-sourcing platform and validated this idea on a set of user-generated voice-based commands.…”
Section: End-user Elicitation Studiesmentioning
confidence: 99%
See 2 more Smart Citations